2020
DOI: 10.1371/journal.ppat.1008296
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of herpes simplex virus reactivation in vivo results in neuronal destruction

Abstract: A fundamental question in herpes simplex virus (HSV) pathogenesis is the consequence of viral reactivation to the neuron. Evidence supporting both post-reactivation survival and demise is published. The exceedingly rare nature of this event at the neuronal level in the sensory ganglion has limited direct examination of this important question. In this study, an in-depth in vivo analysis of the resolution of reactivation was undertaken. Latently infected C57BL/6 mice were induced to reactivate in vivo by hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 84 publications
(129 reference statements)
0
21
0
1
Order By: Relevance
“…This indicates that reactivation proceeds via a Phase I-wave of gene expression in response to multiple different stimuli. However, we note that there may be differences in the mechanism and kinetics of reactivation with different stimuli and/or strains of HSV-1 as reactivation triggered by axotomy or heat shock following infection with a more pathogenic strain of HSV may bypass Phase I or occur more rapidly, making Phase I difficult to detect ( Cliffe and Wilson, 2017 ; Liang et al, 2009 ; Doll et al, 2020 ). It will be especially interesting to determine in the future whether there are differences in the progression to reactivation with different strains of HSV, further elucidate the underlying progression to reactivation and requirements for Phase I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that reactivation proceeds via a Phase I-wave of gene expression in response to multiple different stimuli. However, we note that there may be differences in the mechanism and kinetics of reactivation with different stimuli and/or strains of HSV-1 as reactivation triggered by axotomy or heat shock following infection with a more pathogenic strain of HSV may bypass Phase I or occur more rapidly, making Phase I difficult to detect ( Cliffe and Wilson, 2017 ; Liang et al, 2009 ; Doll et al, 2020 ). It will be especially interesting to determine in the future whether there are differences in the progression to reactivation with different strains of HSV, further elucidate the underlying progression to reactivation and requirements for Phase I.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 T cells have been linked to controlling HSV reactivation ( Divito et al, 2006 ), and regulatory T cells have been found to facilitate HSV reactivation in an in vivo model by suppressing CD8 T cells ( Yu et al, 2018 ). However, a recent in vivo study found that Iba+ phagocytic cells play a key role clearing reactivating neurons ( Doll et al, 2020 ), which required viral DNA replication. HSV latency is not fully silent, with detectible lytic gene expression in infected neurons ( Ma et al, 2014 ; Singh and Tscharke, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models of peripheral HSV1 infection already exist such as the rabbit and mouse eye models and the guinea pig models ( 164 , 165 ). These models have been widely used to study multiple aspects of HSV1 biology, including viral reactivation in the PNS ( 166 170 ). However, they have rarely been used to investigate the direct role of herpesvirus-induced neuroinflammatory responses in the PNS in initiating AD in the brain.…”
Section: Neuroinflammation: At the Center Of The Infectious Hypothesimentioning
confidence: 99%
“…This indicates that reactivation proceeds via a Phase 1-wave of gene expression in response to multiple different stimuli. However we note that there may be differences in the mechanism and kinetics of reactivation with different stimuli and/or strains of HSV-1 as reactivation triggered by axotomy may bypass Phase I 19,20 and reactivation induced in vivo by heat shock with a more pathogenic strain of HSV triggered more rapid reactivation 71 . It will be especially interesting to determine in the future whether there are differences in the progression to reactivation with different strains of HSV.…”
Section: Discussionmentioning
confidence: 88%